Effective Antitumor of Orally Intestinal Targeting Penetrating Peptide-Loaded Tyroserleutide/PLGA Nanoparticles in Hepatocellular Carcinoma - Ma C (Dove Medical Press, 2021)
Chenjun Ma, Tiantian Wei, Yingying Hua, Zhongjie Wang, Liefeng Zhang School of Food and Pharmaceutical Engineering, Nanjing Normal University, Nanjing, 210046, People’s Republic of ChinaCorrespondence: Liefeng Zhang Wenyuan Road 1#, Qixia District, Nanjing, 210046, People’s Republic of ChinaTel +86-25-85898184Fax +86-25-85898184Email lfzhang@njnu.edu.cnPurpose: Hepatocellular carcinoma (HCC) is a common malignant tumor that seriously threatens human life and health. Currently, the majority of antitumor drugs are administered in an injectable manner, which can cause pain and side effects to patients. Objective of this study is to establish an effective oral drug delivery system for anti hepatoma drugs.Methods: In this study, intestinal targeting cell penetrating peptide (R6LRVG) was obtained by binding cell penetrating peptide (R6) with the polypeptide of LRVG (targeting intestinal epithelial cells). Next, R6LRVG-modified tyroserleutide-poly(lactic-co-glycolic acid) (PLGA) nanoparticles (YSL-PLGA/R6LRVG NPs) were prepared. After that, the nanoparticles were characterized and their stability was evaluated. The cellular uptake, in vitro bioactivity and in vivo antitumor activity of the nanoparticles were investigated. In addition, the mechanism, including the endocytic pathway and respiratory rate detection of mitochondria, was further investigated.Results: YSL-PLGA/R6LRVG NPs were successfully prepared. Characterization revealed YSL-PLGA/R6LRVG NPs to be globular particles with smooth surfaces and an average diameter of 222.6 nm. The entrapment efficiency and drug loading of tyroserleutide were 70.27% and 19.69%, respectively. Furthermore, the YSL-PLGA/R6LRVG NPs group exhibited the largest amount of YSL uptake. We also found that cell uptake of YSL-PLGA/R6LRVG NPs could be related to the endocytosis pathways mediated by reticulin and caveolae/lipid rafts. Additionally, the YSL-PLGA/R6LRVG NPs could interfere with mitochondrial function. In vivo experiments revealed that orally administered YSL-PLGA/R6LRVG NPs exerted excellent anticancer effects in tumor-bearing mice. Hematoxylin-eosin staining did not show any histological changes in the major organs.Conclusion: To summarize, YSL-PLGA/R6LRVG NPs could be a useful oral delivery system of YSL and may provide a new platform for the oral delivery of anticancer drugs.Keywords: nanoparticles, target penetrating peptide, tyroserleutide, hepatocellular carcinoma, cellular respiration rate